2009
DOI: 10.1093/nar/gkp668
|View full text |Cite
|
Sign up to set email alerts
|

A search for small noncoding RNAs in Staphylococcus aureus reveals a conserved sequence motif for regulation

Abstract: Bioinformatic analysis of the intergenic regions of Staphylococcus aureus predicted multiple regulatory regions. From this analysis, we characterized 11 novel noncoding RNAs (RsaA‐K) that are expressed in several S. aureus strains under different experimental conditions. Many of them accumulate in the late-exponential phase of growth. All ncRNAs are stable and their expression is Hfq-independent. The transcription of several of them is regulated by the alternative sigma B factor (RsaA, D and F) while the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
337
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(353 citation statements)
references
References 106 publications
15
337
1
Order By: Relevance
“…4 This position is likely a transcriptional start since (i) a 5' RACE performed in the absence of TAP treatment shows a highly reduced level of first strand synthesized cDNA (Fig. 1B) and (ii) a potential -10 and -35 transcription promoter, conserved in other Staphylococcus is present upstream of the identified transcriptional start (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…4 This position is likely a transcriptional start since (i) a 5' RACE performed in the absence of TAP treatment shows a highly reduced level of first strand synthesized cDNA (Fig. 1B) and (ii) a potential -10 and -35 transcription promoter, conserved in other Staphylococcus is present upstream of the identified transcriptional start (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…2 The ncRNA RsaOG (acronym for RNA S. aureus Orsay G) was initially discovered in a bioinformatics ncRNA screen of the S. aureus genome 3 and confirmed in a second study. 4 Here, we show that it is the founding member of a new trans-acting ncRNA family conserved in all Staphylococcaceae. We define the rsaOG gene boundaries and analyze its RNA sequence alignment, structure and phylogeny.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…23 Consistently, Crich loop sequences are a common feature among sRNAs and it was postulated that these motifs generally are signatures of sRNAs that repress the translation of target mRNAs by pairing with the RBS. 24 An example is RNAIII, a sRNA which is predominant in Staphylococcus species. RNAIII harbors a conserved motif, UCCC, in 3 of its hairpin loops.…”
Section: Discussionmentioning
confidence: 99%
“…25 Moreover, in a comparative study in S. aureus strains, several distinct sRNAs were identified that carry the identical Crich loop motif. 24 The authors hypothesized that these sRNAs are the product of convergent evolution. A similar picture is found in S. meliloti where several representatives of RNA families occur which are either similar to cuckoo HP2 (RFM SmelA003 ), cuckoo HP3 (RFM SmelB008 , RFM SmelC416 , RFM SmelC601 ) or cuckoo HP4 (RFM SmelC023 ) RNAs.…”
Section: Discussionmentioning
confidence: 99%